"Education should be linked with emotions": Interview with Alberto Dittborn - Brancoli , Bernardita (Base Diseño e Innovación, 2016)
Away from the city and in the midst of nature, this designer defines his profession as a privilege that, because it is unimportant, enables you to see what others cannot. And it is precisely this aspect that he stands out of the link that he or his colleagues may have with education: teaching to read around experiences.